Correlation Between Albumin Level and 28-Days Sepsis Related Mortality - Nugroho H.S.; Mafiana R; Irwanto FH; Husin Syarif (HM Publisher, 2021)
Introduction: The mortality rate from sepsis is much greater than that from acute coronary syndrome or stroke. Uncontrolled release of cytokines (abnormalities in the inflammatory response) such as TNF-α and IL-1, IL-6 can reduce serum albumin level, so that the presence of hypoalbuminemia conditions can indicate how the inflammatory reaction occurs in septic patients. Albumin can be a predictor of mortality in septic patients. This study aims to determine the correlation between serum albumin level and the 28-day mortality of patients with sepsis. Methods: This study is an analytical observational study with a retrospective cohort design. The research was conducted in September 2020 until the completion of data collection at dr. Mohammad Hoesin Hospital Palembang. The sample in this study were all sepsis patients in the intensive care unit who were registered in the Medical Record Installation of dr. Mohammad Hoesin Hospital Palembang from 1 January 2019 to 31 December 2019 met the inclusion and exclusion criteria. After the data was collected, analysis was carried out using the STATA program. Results: The serum albumin value ≤ of 2.6 mg / dL on the fourth day was significant with the mortality of septic patients. Patients with a serum albumin value ≤ 2.6 mg / dL had a risk of 1.288 times experiencing death compared to an albumin value> 2.6 mg / dL. Albumin in the fourth day had moderate correlation with sepsis patient mortality (r = 0.497; p = 0.001) Conclusion: Albumin serum on the fourth day had a moderate correlation with 28 days sepsis patient mortality